2017
DOI: 10.1097/brs.0000000000001889
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Supine MRI With a Lumbar Pillow—An Alternative to Weight-bearing MRI for Diagnosing Spinal Stenosis?

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Lumbar extension seems to aggravate spinal canal stenosis related to degenerative changes. 38 A similar affect may be achieved by scanning in the supine position with a pillow behind the lumbar spine with 21,49 or without axial loading. 38 Whether WBMRI provides added information over scanning in the supine extended position is not clear.…”
Section: Weight-bearing Mri Of the Lumbar Spinementioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar extension seems to aggravate spinal canal stenosis related to degenerative changes. 38 A similar affect may be achieved by scanning in the supine position with a pillow behind the lumbar spine with 21,49 or without axial loading. 38 Whether WBMRI provides added information over scanning in the supine extended position is not clear.…”
Section: Weight-bearing Mri Of the Lumbar Spinementioning
confidence: 99%
“…30,36,37 Also, many of the degenerative pathologies seen on supine MRI imaging are more evident in the upright position. 36,38 WBMRI seems to exaggerate, to a varying degree, most degenerative spinal pathologies such as segmental instability (olisthesis, scoliosis) 36 and disk degenerative morphology (disk height, 37,39-41 disk bulging, protrusion, extrusion, 30,40,[42][43][44] high-intensity zone tears, 45 spinal stenosis, 36,38,45 and ligamentum flavum bulging 46 ) (►Figs. 3 and 4).…”
Section: Weight-bearing Mri Of the Lumbar Spinementioning
confidence: 99%
“…In contrast, studies indicated that standing weight-bearing MRI and supine MRI with a lumbar pillow hyperextending the lumbar spine may result in similar morphological changes in the ligamentum flavum with reduction in spinal canal dimensions. 8,9 However, examining patients with a lumbar pillow can be painful. 8 These findings suggest that lumbar extension is an important dynamic contributor to symptomatology in spinal stenosis.…”
Section: Changes In the Ligamentum Flavummentioning
confidence: 99%
“…8,9 However, examining patients with a lumbar pillow can be painful. 8 These findings suggest that lumbar extension is an important dynamic contributor to symptomatology in spinal stenosis.…”
Section: Changes In the Ligamentum Flavummentioning
confidence: 99%
“…Weight bearing MRI (WB-MRI) scanners of various designs have recently become available. Using a i.e., a tilting low-field magnet of 0.25 T, supine and upright WB-MRI of the knee, spine and foot can be performed with potential added diagnostic value in selected pathologies 37,38 . Supine imaging of the spine in the WB-MRI system has also shown to have equal diagnostic potential in degenerative spine disease compared to high-field MRI examinations 39 .…”
Section: Diagnosismentioning
confidence: 99%